AfroAsian Musical Imaginaries: Of Circulations and Interconnections - Kumar, Rakesh (International Library of African Music, 2025)
pages: 83-86
Keywords: Book reviews; Afro-Asian Music; Cultural Circulation; Musical Imaginaries; African Music